Analisis Principal Component Analysis (PCA) dalam Penentuan Faktor Kepuasan Pengunjung terhadap Layanan Perpustakaan Digilib - Sudianto Manullang; Dita Aryani; Hanifah Rusydah (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Maximum management of the library, especially improving services to users is a must that needs to be evaluated by the library manager. Visitor satisfaction is difficult to measure because it relates to the high and low expectations of visitors to the service they want. The purpose of this study is to investigate the most important factors or components in aspects of visitor satisfaction. So that it can increase satisfaction appropriately so that the library can carry out the right strategy to maintain and provide the best quality service. The subjects of this study were students with 2019 – 2022 status. 120 samples were taken using a random sampling technique. The collected data will be analyzed using the Principal Component Analysis (PCA) method. The PCA analysis process was carried out in several stages, namely the Bartlett's test, testing the KMO value, testing the correlation matrix, PCA analysis, and interpreting the PCA results. Findings from PCA analysis by reducing 12 correlated variables into 2 factors, namely reference services and facilities and infrastructure. The results of this study indicate that the facilities and infrastructure factor have a greater cumulative percentage of variance compared to the reference service factor, which is equal to 51,387%.